2008
DOI: 10.1186/1471-2407-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of VEGF-C and COX-2 and its association with lymphangiogenesis in human breast cancer

Abstract: BackgroundLymphangiogenesis has become a new research frontier in tumor metastasis since the discovery of reliable lymphatic markers that have allowed observation and isolation of lymphatic endothelium. Cyclooxygenase-2 (COX-2) has been reported to be involved in the critical steps in carcinogenesis. However, possible role of COX-2 in lymphangiogenesis and lymphatic metastasis is still poorly understood. In present study, we aimed to investigate the relationship between vascular endothelial growth factor-C (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 26 publications
4
55
0
1
Order By: Relevance
“…PGE 2 can modulate VEGF synthesis through the EP3 receptor [73]. Cox-2 expression is positively correlated with high VEGF levels in patients with multiple types of cancer and is associated with increased angiogenesis and metastasis [74,75]. Therefore, use of Cox-2 selective inhibitors could potentially reduce growth factor levels, thereby reducing angiogenesis.…”
Section: Cox-2/pge 2 Promotes Angiogenesis and Metastasismentioning
confidence: 99%
“…PGE 2 can modulate VEGF synthesis through the EP3 receptor [73]. Cox-2 expression is positively correlated with high VEGF levels in patients with multiple types of cancer and is associated with increased angiogenesis and metastasis [74,75]. Therefore, use of Cox-2 selective inhibitors could potentially reduce growth factor levels, thereby reducing angiogenesis.…”
Section: Cox-2/pge 2 Promotes Angiogenesis and Metastasismentioning
confidence: 99%
“…Molecular investigations of breast cancer tissues provide strong evidence that COX-2-derived PGE-2 stimulates the synthesis and release of VEGF resulting in angiogenesis and ingrowth of new blood vessels that are immature and highly permeable thereby facilitating metastatic spread of tumor cells [7,28,154] . Tumor secretion of VEGF (and other growth factors) may further amplify COX-2 expression in a positive feedback loop to produce lymphangiogenesis [155,156] . Notably, inhibition of this vicious cycle by COX-2 inhibiting agents such as celecoxib has been found to limit angiogenesis and halt the progression and metastatic spread of tumors in animals [157] .…”
Section: Angiogenesismentioning
confidence: 99%
“…[18][19][20] However, recent evidence clearly reveals that expression of VEGF-C 9,17,21 or VEGF-D 22 in human breast cancer in situ is strongly correlated with lymphangiogenesis, lympho-vascular invasion and lymphatic metastasis. In addition to its role in promoting lymphangiogenesis, we found that VEGF-C production by breast cancer cells served as an autocrine stimulus for their motility by binding to a diverse group of VEGF-C receptors.…”
mentioning
confidence: 99%